A clozapine-induced hypersensitivity reaction. (17th June 2020) - Curtis, L.; Hallahan, B.; Byrne, F.
Abstract : A 57-year-old female patient with a diagnosis of schizo-affective disorder since 1986 was commenced on clozapine due to persistent positive and negative psychotic symptoms in September 2014. After commencement of clozapine she was delusion free and demonstrated an improvement in negative symptoms. Three months after commencement of clozapine she developed a hypersensitivity reaction. Her symptoms continued to deteriorate despite being prescribed an anti-histamine. Clozapine was discontinued 6 days after the appearance of a generalised pruritic rash, as it was believed to be the probable cause. There was complete resolution of symptoms 1 week after discontinuation of clozapine. Clozapine was replaced with olanzapine and amisulpride. There has been no similar cutaneous or allergic reactions for the past 30 months.